2016
DOI: 10.1055/s-0035-1570755
|View full text |Cite
|
Sign up to set email alerts
|

The Practice of Anal Dilations following Anorectal Reconstruction in Patients with Anorectal Malformations: An International Survey

Abstract: The objective of this study was to investigate the current practices of anal dilations after anorectal reconstruction for anorectal malformations (ARMs) in different centers. An online survey, consisting of 27 questions about the practice of anal dilations, was launched in March 2015 among 54 pediatric surgeons with expertise in colorectal surgery. The survey was divided into three sections. The first section included questions regarding the country of origin, the role in the department, the average number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 12 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…This is similar to the generally established practice of starting anal dilation at about the 14 th post-operative day. [ 8 , 9 ] All of our patients who completed the dilation within the study period achieved and maintained the desired anal calibre within an average of about 7 months, similar to the recommended Pena anal dilation protocol duration. [ 2 , 3 ]…”
Section: Discussionmentioning
confidence: 70%
“…This is similar to the generally established practice of starting anal dilation at about the 14 th post-operative day. [ 8 , 9 ] All of our patients who completed the dilation within the study period achieved and maintained the desired anal calibre within an average of about 7 months, similar to the recommended Pena anal dilation protocol duration. [ 2 , 3 ]…”
Section: Discussionmentioning
confidence: 70%
“…Until recently, routine postoperative anal dilations have been recommended for all patients after a primary PSARP to prevent a postoperative stricture [83][84][85][86]. In 2021, Ahmad et al reported no significant reduction in stricture formation in patients dilated after reconstruction [87].…”
Section: Heineke-mikulicz-like Anoplastymentioning
confidence: 99%